ABA accumulation in water-stressed Citrus roots does not rely on carotenoid content in this organ. (November 2016) - Manzi, Matías; Lado, Joanna; Rodrigo, María Jesús; Arbona, Vicent; Gómez-Cadenas, Aurelio
Highlights: Detached Citrus roots exposed to water deficit are unable to de novo synthetize ABA. β, β-carotenoids in roots do not contribute to accumulate ABA upon dehydration. Carotenoids in roots sharply decreases in response to dehydration. Dehydration upregulates carotenoid and ABA related genes irrespective of precursors. Light modulates the expression of specific genes in roots. Abstract: Sustained abscisic acid (ABA) accumulation in dehydrated citrus roots depends on the transport from aerial organs. Under this condition, the role of the β, β-carotenoids (ABA precursors) to the de novo synthesis of ABA in roots needs to be clarified since their low availability in this organ restricts its accumulation. To accomplish that, detached citrus roots were exposed to light (to increase their carotenoid content) and subsequently dehydrated (to trigger ABA accumulation). Stress imposition sharply decreased the pool of β, β-carotenoids but, unexpectedly, no concomitant rise in ABA content was observed. Contrastingly, roots of intact plants (with low levels of carotenoids) showed a similar decrease of ABA precursor together with a significant ABA accumulation. Furthermore, upon dehydration both types of roots showed similar upregulation of the key genes involved in biosynthesis of carotenoids and ABA ( CsPSY3a ; CsβCHX1 ; CsβCHX2 ; CsNCED1 ; CsNCED2 ), demonstrating a conserved transcriptional response triggered by water stress. Thus, the sharp decrease in root carotenoid levels in response to dehydration should be related to other stress-related signals instead of contributing to ABA biosynthesis. In summary, ABA accumulation in dehydrated-citrus roots largely relies on the presence of the aerial organs and it is independent of the amount of available root β, β-carotenoids.